2009
DOI: 10.1007/s00276-009-0493-z
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Tuffier’s line evaluated on cadaver specimens

Abstract: The aim was to evaluate the reliability of Tuffier's line usually used as sole method to identify lumbar spinous process for a correct needle placement. Fifty-eight cadaver specimens were placed in a lateral position and a flexion in the lumbar spine performed to achieve a neutralization of the lumbar lordosis. The iliac crests were palpated and the lumbar spinous process marked on the intercristal line with a pin; all specimens were dissected and the marked spinous process documented. The center of the L4 spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
2
8
0
5
Order By: Relevance
“…MR imaging studies demonstrated that the Tuffier's line were in a significantly lower position in females compared to males in adults [4,8]. A similar result demonstrated by Windisch et al in a cadaveric study [9]. Shiraishi et al who found that the intercristal line passes through the body and lower one-third of L4 in men and the body and upper one-third of L5 in women [10].…”
Section: Discussionsupporting
confidence: 66%
“…MR imaging studies demonstrated that the Tuffier's line were in a significantly lower position in females compared to males in adults [4,8]. A similar result demonstrated by Windisch et al in a cadaveric study [9]. Shiraishi et al who found that the intercristal line passes through the body and lower one-third of L4 in men and the body and upper one-third of L5 in women [10].…”
Section: Discussionsupporting
confidence: 66%
“…Both conus medullaris and Tuffier's line have been reported to be placed slightly lower down more frequently in females than in males [9]. To date we are unaware of any study demonstrating gender differences in the conus-Tuffier's line distance.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the Tuffier line in females in the control group with no fracture was determined at lower levels. In a study of 58 cadavers by Windisch et al, it was reported that the Tuffier line in females was usually at a lower level than that of males [11]. It has been reported that the Tuffier line is at a lower level in females than in males, independently of age, as the anatomic structure of the pelvic bones of females is different from that of males [12].…”
Section: Discussionmentioning
confidence: 99%